(untitled) (Zaporizhzhia Historical Review, 2021)
This article is about singularity and originality of journal “Kyiv Antiquity”, which had been existing since 1882 until 1906. This journal had great meaning for development of social politic movement and national revival. Its contribution in history, archeology and study and publication of early texts was very important. Influence of that periodical edition on development of Ukrainian language is also reflected.